Effects of mechanical recycling on the properties of glass fiber-reinforced polyamide 66 composites in automotive components - Gulturk, Cansu; Berber, Hale (DE GRUYTER POLAND SP Z O O, 2023)
In this study, we aimed to reveal the effective reusability of waste generated during the injection molding process of polyamide 66 (PA66) reinforced with 30 wt% of short glass fiber (PA66-GF30) widely used in the automotive industry. PA66-GF30 was subjected to the three mechanical recycling cycles, including regranulation and reinjection molding steps, and the recycled materials obtained in each of these cycles were included at the ratios of 15, 20, 25, and 30 wt% to the virgin composite. Thermogravimetric analysis and differential scanning calorimeter analyses showed that the number of recycling cycles and recycled material content in the composite had no significant change in the thermal stability and crystallinity degree of the PA66-GF30. The average fiber length determined by optical microscope analysis shifted to lower values from 300-350 to 150-250 mu m by increasing the number of recycling cycles and the recycled material content. The fact that the recycled material content in the composite exceeds 25 wt% and the recycling cycle is applied three times played a key role in changing the mechanical and melt flow behaviors of the composite. Tensile strength, elastic modulus, and impact energy slightly decreased while the elongation at break and melt flow index increased.
Keywords: mechanical recycling; polyamide 66; glass fiber-reinforced composites; automotive components; injection molding; TENSILE-STRENGTH; LENGTH; IMPACT; CRYSTALLIZATION; DIAMETER; POLYMERS; BEHAVIOR; PLASTICS; Polymer Science